Tuning Pt-CeO2 interactions by high-temperature vapor-phase synthesis for improved reducibility of lattice oxygen - Pereira-Hernández, Xavier Isidro; DeLaRiva, Andrew; Muravev, Valery; Kunwar, Deepak; Xiong, Haifeng; Sudduth, Berlin; Engelhard, Mark; Kovarik, Libor; Hensen, Emiel J. M.; Wang, Yong; Datye, Abhaya K. (Nature communications, 2019)
In this work, we compare the CO oxidation performance of Pt single atom catalysts (SACs) prepared via two methods: (1) conventional wet chemical synthesis (strong electrostatic adsorption–SEA) with calcination at 350 °C in air; and (2) high temperature vapor phase synthesis (atom trapping–AT) with calcination in air at 800 °C leading to ionic Pt being trapped on the CeO 2 in a thermally stable form. As-synthesized, both SACs are inactive for low temperature (<150 °C) CO oxidation. After treatment in CO at 275 °C, both catalysts show enhanced reactivity. Despite similar Pt metal particle size, the AT catalyst is significantly more active, with onset of CO oxidation near room temperature. A combination of near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS) and CO temperature-programmed reduction (CO-TPR) shows that the high reactivity at low temperatures can be related to the improved reducibility of lattice oxygen on the CeO 2 support. While single-atom catalysts (SACs) have attracted a lot of interest, the nature of the active sites in SACs remains elusive. Here the authors elucidate that depositing single atoms via high temperature synthesis leads to improved reducibility of lattice oxygen on CeO2 yielding low temperature reactivity of Pt catalysts in CO oxidation.